Peningkatan Literasi Finansial Petani Tomat Beef Hidroponik melalui Edukasi Break Even Point (BEP) dan Pengembangan Aplikasi Simulasi Harga Jual Berbasis Android - Indri Utami; Ayi Astuti; Dudi Yudha Kusuma; Stefhani Ahtarisa; Alyudi (Jurnal Pengabdian Tri Bhakti, 2026)
The sustainability of horticultural farming businesses, particularly hydroponic beef tomato cultivation, is determined not only by technical production performance but also by farmers’ ability to manage the financial aspects of their operations. Low levels of financial literacy make it difficult for farmers to identify cost structures, set rational selling prices, and anticipate market price fluctuations. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance the financial literacy of hydroponic beef tomato farmers through Break-Even Point (BEP) education and assistance in using an Android-based selling price simulation application. The program employed a participatory and educational approach, including training sessions, practical assistance, and monitoring and evaluation in collaboration with the Agrotani Lembang farmer group. The results indicate an improvement in farmers’ understanding of production costs, their ability to independently calculate BEP, and the adoption of simple financial record-keeping practices. Furthermore, the use of digital applications supports farmers in conducting price simulations and making data-driven business decisions. These findings demonstrate that the integration of financial education and digital technology is effective in improving efficiency and supporting the sustainability of hydroponic farming enterprises.